PRIMARY SOURCES REFLECTING THE HISTORY OF “LAYLI AND MAJNUN” - Turdiyeva, Maftuna (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The subject and characters of certain works have a historical significance in the history of literature. There are various interpretations and sources that have influenced these classic works, since they have already transformed into literary masterpieces. The skillful creators transform the beautiful story or narrative into a magnificent work of art in various interpretations. One of these works is the story of "Layla and Majnun." It is one of the sad stories created in world literature which has been written by dozens of authors and folk artists, has finally spread widely among the peoples of the Near and Middle East. This epic has a complex history spanning many centuries. As Krachkovskiy emphasized, its background goes to the second half of the 7th century. It first appeared in ancient Arabic manuscripts that emerged among the Arabs. There are different versions of this story, which can be found in some sources. The study deals with the first sources that depicted the story of "Layla and Majnun," as well as the book that provides extensive information about this story – Qays ibn Mulavvah – Majnun in Abul Faraj Isfakhani’s “Book of songs”, and Majnun’s poems.